Sns and Kirre, the Drosophila orthologs of Nephrin and Neph1, direct adhesion, fusion and formation of a slit diaphragm-like structure in insect nephrocytes. - Zhuang, S.; Shao, H.; Guo, F.; Trimble, R.; Pearce, E.; Abmayr, S.M. (Development, 2009)
The Immunoglobulin superfamily (IgSF) proteins Neph1 and Nephrin are co-expressed within podocytes in the kidney glomerulus, where they localize to the slit diaphragm (SD) and contribute to filtration between blood and urine. Herein, we demonstrate that their Drosophila orthologs Kirre (Duf) and Sns are co-expressed within binucleate garland cell nephrocytes (GCNs) that contribute to detoxification of the insect hemolymph by uptake of molecules through an SD-like nephrocyte diaphragm (ND) into labyrinthine channels that are active sites of endocytosis. The functions of Kirre and Sns in the embryonic musculature, to mediate adhesion and fusion between myoblasts to form multinucleate muscle fibers, have been conserved in the GCNs, where they contribute to adhesion of GCNs in the ;garland' and to their fusion into binucleate cells. Sns and Kirre proteins localize to the ND at the entry point into the labyrinthine channels and, like their vertebrate counterparts, are essential for its formation. Knockdown of Kirre or Sns drastically reduces the number of NDs at the cell surface. These defects are associated with a decrease in uptake of large proteins, suggesting that the ND distinguishes molecules of different sizes and controls access to the channels. Moreover, mutations in the Sns fibronectin-binding or immunoglobulin domains lead to morphologically abnormal NDs and to reduced passage of proteins into the labyrinthine channels for uptake by endocytosis, suggesting a crucial and direct role for Sns in ND formation and function. These data reveal significant similarities between the insect ND and the SD in mammalian podocytes at the level of structure and function.